Robust disturbance rejection control of a biped robotic system using high-order extended state observer. (May 2016) - Martínez-Fonseca, Nadhynee; Castañeda, Luis Ángel; Uranga, Agustín; Luviano-Juárez, Alberto; Chairez, Isaac
Abstract: This study addressed the problem of robust control of a biped robot based on disturbance estimation. Active disturbance rejection control was the paradigm used for controlling the biped robot by direct active estimation. A robust controller was developed to implement disturbance cancelation based on a linear extended state observer of high gain class. A robust high-gain scheme was proposed for developing a state estimator of the biped robot despite poor knowledge of the plant and the presence of uncertainties. The estimated states provided by the state estimator were used to implement a feedback controller that was effective in actively rejecting the perturbations as well as forcing the trajectory tracking error to within a small vicinity of the origin. The theoretical convergence of the tracking error was proven using the Lyapunov theory. The controller was implemented by numerical simulations that showed the convergence of the tracking error. A comparison with a high-order sliding-mode-observer-based controller confirmed the superior performance of the controller using the robust observer introduced in this study. Finally, the proposed controller was implemented on an actual biped robot using an embedded hardware-in-the-loop strategy. Abstract : Highlights: A novel Lyapunov function is given to prove the stability of active disturbance rejection control. Generalized proportional integral observers are used to solve the robust controller. The problem of trajectory tracking of biped robots is solved using the proposed controller. Numerical and experimental tests show the effectiveness of the suggested controller. Comparison against a robust technique (sliding modes) are provided.